PENGARUH PENGUNGKAPAN CSR TERHADAP KINERJA KEUANGAN PT. ASAHIMAS FLAT GLASS TBK - Sinta Ayu Kelana; Ramdany Ramdany (STIE Muhammadiyah Jakarta, 2020)
CSR disclosure is one of the efforts made by the company to build trust in stakeholders so that investors are interested in investing their capital in the company. The purpose of this study is to analyze the disclosure of social and environmental responsibility that will be tested whether there is an influence on the company's financial performance. The financial performance of the company in this study is proxied by the variable ROA. In this study, the type of data used is secondary data taken from annual financial reports that have been published on the Indonesia Stock Exchange. This study uses a data sample of 6 years from 2011 to 2016. The results of this study indicate that the level of social and environmental responsibility disclosure affects ROA.